Programme d'aide à la transition selon les personnalités vocationnelles: particularités et fondements - Riverin-Simard, Danielle; Riverin, Jacinthe (Canadian Journal of Counselling and Psychotherapy, 1993)
The objective of this article is to present a brief survey of the content of the work entry assistance program entitled: "Strategies of occupational transitions and vocational personalities." Practitioners and researchers are thus provided with a general outline of the particularities and foundations of this program, including the innovative aspects, the targeted clients, the educative approach employed, the techniques proposed and the key concepts. Lastly, in terms of practical application, several steps are proposed with regards to the necessity of providing specific training for those interested in the application of this assistance program.